In situ syntheses of hydroxyapatite‐grafted graphene oxide composites. Issue 9 (18th May 2019) - Iacoboni, Ilaria; Perrozzi, Francesco; Macera, Ludovico; Taglieri, Giuliana; Ottaviano, Luca; Fioravanti, Giulia
Abstract: In this study, we examined three different syntheses of hydroxyapatite (HAp) and graphene oxide–hydroxyapatite (GO–HAp) composites with a GO content of 9, 33, and 43% wt. The materials were prepared from various precursors of calcium and phosphate ions, using an in situ synthesis method, with mild conditions to avoid reducing the GO. In situ bonding technology proposed that calcium ions bond with GO at first and then HAp nanoflakes in situ grow on GO sheets, forming GO–HAp nanocomposite. The aim of the present work was to analyze the differences due to the use of different starting reagents and verify, with the addition of increasing amounts of GO, the changes in morphology, crystallinity, and solubility of the obtained HAp composites. Detailed structural and morphological characterization studies of the composites were carried out using scanning electron microscopy, energy dispersive X‐ray spectrometry, X‐ray powder diffraction, Raman spectroscopy, and Fourier transform infrared spectroscopy. We found that GO sheets act as a nucleation site for HAp mineralization, but we observed a loss of the crystallographic order due to the intercalation of the graphenic sheets between the HAp particles.